2004
DOI: 10.1177/1087057104263913
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Small-Molecule Inhibitors for Human Transketolase by High-Throughput Screening with Fluorescent Intensity (FLINT) Assay

Abstract: The metabolic enzyme transketolase (TK) plays a crucial role in tumor cell nucleic acid synthesis, using glucose through the elevated nonoxidative pentose phosphate pathway (PPP). Identification of inhibitors specifically targeting TK and preventing the nonoxidative PPP from generating the RNA ribose precursor, ribose-5-phosphate, provides a novel approach for developing effective anticancer therapeutic agents. The full-length human transketolase gene was cloned and expressed in Escherichia coli and the recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Metabolic control analysis and inhibition of transketolase enzyme reactions have already shown that tumor proliferation can be inhibited by anti-transketolase approaches. 9,17 The most effective way to inhibit tumour proliferation should be to block the generation of energy for tumor growth. We believe future TKTL1 gene might become a novel hot spot of study in anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic control analysis and inhibition of transketolase enzyme reactions have already shown that tumor proliferation can be inhibited by anti-transketolase approaches. 9,17 The most effective way to inhibit tumour proliferation should be to block the generation of energy for tumor growth. We believe future TKTL1 gene might become a novel hot spot of study in anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective way to inhibit tumour proliferation should be to block the generation of energy for tumour growth. Metabolic control analysis and inhibition of transketolase enzyme reactions have already shown that tumour proliferation can be inhibited by anti-transketolase approaches (Rais et al, 1999;Boros et al, 2001a, b;Comin-Anduix et al, 2001Du et al, 2004). These successful results have been attributed to TKT transketolase.…”
Section: Discussionmentioning
confidence: 99%
“…This approach resulted in the identification of two novel small-molecule inhibitors, which inhibit human TKT and suppress proliferation of cancer cell lines (Du et al, 2004).…”
mentioning
confidence: 99%
“…Similar to the relevance of Her2/neu as a 'drugable' target for an individualized anti-cancer therapy (22)(23)(24)(25), TKTL1 might also be a future target for small molecule drug design and individualized treatment strategies in breast cancer: metabolic control analysis and inhibition of transketolase enzyme reactions have shown in vitro as well as in vivo that tumor proliferation can be inhibited by antitransketolase approaches (5)(6)(7)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%